Kritik Orientalis dalam Aspek Ontologis Studi Al-Qur’an - Muttaqin Muttaqin; Moh Agung Fambudi (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This article analyzes the Orientalists who study the Qur'an, they are Abraham Geiger, Theodore Noldeke, William Muir, and John Wansbrough. This research uses descriptive analysis methods to find out how Orientalists view and think about the Qur'an. The main data is collected from books related to Orientalist thought as well as from scientific journals. The results found several Orientalist views of the Qur'an in the ontological aspect. Geiger argues that the Qur'an is influenced by Judaism which includes: various stories in the Qur’an, morals, and laws, about life, language, and faith. The Prophet Muhammad took a lot of Jewish cultures and integrated them into Islam. Meanwhile, Noldeke alleged that the Qur'an was composed by the Prophet Muhammad and that many of its contents were plagiarized from the Bible. His criticism of the Qur'an can be summarized in two points. First, he stated that the meaning of the ummiy of Rasulullah was not unable to read and write, but the opposite of ahl kitab. Second, according to him, the Qur'an is not a revelation. Muir attempted to rearrange the chronology of the Qur'an from a historical perspective and initiated a chronological theory. Meanwhile, John considers the Qur'an not as a holy book but as a collection of notes on the prophetic concepts of the Arab nation and aims to elevate the status of the Arab nation.